Energy, exergy and economic optimization application of integrated dual-loop organic rankine cycle: A case of shopping mall power plant - Muhammed Taha TOPCU; Alperen TOZLU; Kadir BİLEN (Case Studies in Thermal Engineering)
This paper presents a thermoeconomic analysis of the Dual-Loop Organic Rankine Cycle (DORC) integrated into the Erzurum Mall Power Plant (EMPP). The DORC system is designed to utilize waste heat at 425 °C and 9 kg/s, producing additional power for the existing plant. The integration of dual-loop ORC systems with different critical temperature fluids into an operational facility is analyzed. High-temperature cycles use working fluids such as Toluene, MDM (octamethylcyclotrisiloxane), n-Nonane, and n-Octane, while refrigerants R236fa, R600a, and R124 are employed in the low-temperature cycles. The designed model demonstrates that up to 11.4 % of the plant's existing capacity can be added as extra power. The Toluene/R600a combination is identified as the best fluid pair, delivering the highest total net power output (653.4 kW), the lowest total cost rate (19.18 $/h), and the highest exergy efficiency (20.18 %). Optimization of the DORC system is performed using the NSGA-II in MATLAB. For the toluene/R600a pair, the optimization results show an increase of 13.52 % in the net power output and decrease of 1.48 % in the total cost rate, which is a significant improvement over the initial results.